Using the knowledge translation framework to change practical care of central catheters in a Brazilian neonatal unit - Gabriela Ramos Ferreira Curan; Edilaine Giovanini Rossetto; Thaíla Corrêa Castral (Journal of Infection in Developing Countries)
Introduction: The use of central catheters in intensive care is essential, but exposes the patient to the risk of a bloodstream infection. Although there is evidence to improve the care for these patients, there is a gap between knowledge and healthcare practices. This study was designed to describe the bundle implementation for central catheters in light of the knowledge translation (KT) conceptual framework in a neonatal unit and assess its impact on care practices with catheters.